2017
DOI: 10.1111/eea.12557
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray computed tomography reveals that intraspecific competition promotes soldier differentiation in a one‐piece nesting termite

Abstract: Investment in soldier production in eusocial lineages involves a trade‐off between maintenance costs and defense benefits. Termites are eusocial insects that live in colonies organized into three castes: primary reproductives, soldiers, and workers or pseudergates. Neotermes chilensis (Blanchard) (Isoptera: Kalotermitidae) is a one‐piece nesting termite that nests and forages in a single piece of wood. Two scenarios may be of importance in a defense context of one‐piece nesting termites: during swarms, when co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…X-ray imaging is a powerful tool to visualize structure and discover novel biological function in diverse systems ranging from the rhythmic pulsations of insect tracheal systems [52] to the four-dimensional morphology of large vertebrates in locomotion [53]. As a tool for non-destructive morphology, X-ray microtomography has helped to identify and classify a number of ant species, including some preserved within amber [54,55], as well as visualize the natural cavities inhabited by small insects [56,57]. Indeed X-ray imaging of artificial ant nest enclosures in the laboratory has been used to study social insect digging and building behaviours; however, using X-rays to examine these behaviours and the 3D spatial nest organization in natural conditions is technically challenging [28].…”
Section: Temnothorax X-ray Imagingmentioning
confidence: 99%
“…X-ray imaging is a powerful tool to visualize structure and discover novel biological function in diverse systems ranging from the rhythmic pulsations of insect tracheal systems [52] to the four-dimensional morphology of large vertebrates in locomotion [53]. As a tool for non-destructive morphology, X-ray microtomography has helped to identify and classify a number of ant species, including some preserved within amber [54,55], as well as visualize the natural cavities inhabited by small insects [56,57]. Indeed X-ray imaging of artificial ant nest enclosures in the laboratory has been used to study social insect digging and building behaviours; however, using X-rays to examine these behaviours and the 3D spatial nest organization in natural conditions is technically challenging [28].…”
Section: Temnothorax X-ray Imagingmentioning
confidence: 99%
“…This approach also displays its usefulness and further progress in the field of entomology (Friedrich et al ). The use of non‐destructive inspection of materials was implemented, for instance, for the identification of different social castes in nests (Aguilera‐Olivares et al ) and for tracking the movement of insects inside nests (Johnson et al ; Jennings & Austin ).…”
Section: Software and Useful Toolkitsmentioning
confidence: 99%
“…zoellneri [ex P. berteroniana- Zizka et al (2013)] and P. chilensis (Molina, 1782) among its hosts (Aguilera-Olivares et al, 2015). In previous work at the same study site (Aguilera-Olivares et al, 2017), we reported that about half of the scapes were occupied by a single colony (unicolonial substrates) and the other half contained between 2 and 9 colonies (multicolonial substrates). Additionally, we observed galleries interconnecting two colonies within a scape which had been blocked with sawdust, probably following an agonistic interaction.…”
Section: Introductionmentioning
confidence: 99%
“…), temperature and seasonality significantly affect hormone and gene expressions (Scharf et al, 2007;Miura and Scharf, 2011) which trigger the differentiation from pseudergate to presoldier instar. This process may also be enhanced by ecological factors such as inter and/or intraspecific competition as a form of induced defense at the colony level (Passera et al, 1996;Aguilera-Olivares et al, 2017).…”
Section: Introductionmentioning
confidence: 99%